Relationship between propulsive force of the arm, body composition and isokinetic muscle strength indicators in surfers - Oliveira Geber, S.; Cavalcante, B. R.; Germano-Soares, A. H.; Cavalcante Figueiredo Montes, R. C.; Oliveira Silva, A. H.; Samuelson Martins Veloso, T.; Leandro da Costa Silva, J. R.; Moura Santos, M. A. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2018)
This study aimed to evaluate the potential relationship between body composition (percentage of fat mass (FM %), fat mass and lean mass), muscle function (e.g., muscles; deltoid side and front, pectoralis major and teres major) and the propulsive force of the arm (PFA). Sixteen competitive surfers (29.1 ± 7.3 years; 1.72 ± 0.06 m; 74.2 ± 1.4 kg) were assessed for height, body mass, body composition (dual-energy-DXA), muscle function and PFA. Pearson correlation analyses were used to verify the relationship between all variables. An inverse correlations were found between PFA and isokinetic parameters to 60o/s: external rotation (peak torque: r = -0.71; p = 0.014; total work: r = -0.75; p = 0.007; power: r = -0.72; p = 0.011) and internal rotation (peak torque: r = -0.61; p = 0.045; total work: r = -0.73; p = 0.010; power: r = -0.61; p = 0.045) and 300o/s: external rotation (peak torque: r = -0.79; p = 0.003; total work: r = -0.84; p<0,001; power: r = -0.81; p = 0.002) and internal rotation (peak torque: r = -0.69; p = 0.017; total work: r = -0.72; p = 0.011; power: r = -0.69; p = 0.017). There was no significant correlation between body composition components and PFA (p>0.05). Although correlations do not imply cause and effect, PFA is not correlated with body composition in surfers and these relationships are inversely related to the parameters of muscle function.